2016
DOI: 10.1155/2016/3472032
|View full text |Cite
|
Sign up to set email alerts
|

Melatoninergic System in Parkinson’s Disease: From Neuroprotection to the Management of Motor and Nonmotor Symptoms

Abstract: Melatonin is synthesized by several tissues besides the pineal gland, and beyond its regulatory effects in light-dark cycle, melatonin is a hormone with neuroprotective, anti-inflammatory, and antioxidant properties. Melatonin acts as a free-radical scavenger, reducing reactive species and improving mitochondrial homeostasis. Melatonin also regulates the expression of neurotrophins that are involved in the survival of dopaminergic neurons and reduces α-synuclein aggregation, thus protecting the dopaminergic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 283 publications
(433 reference statements)
0
44
0
Order By: Relevance
“…Aside from its classical 2 of 20 action on sleep/wake cycles, melatonin has largely been shown to be a pleiotropic molecule [1][2][3][4] with multiple beneficial actions. In agreement, animal studies have shown melatonin to be an effective neuroprotectant in a number of neurodegenerative conditions such as hypoxia/ischemia [5][6][7], Alzheimer's Disease [8], Parkinson's Disease [9], and spinal cord injury [10]. Notably, clinical trials have been designed to establish the potential neuroprotective efficacy of melatonin in humans [11].…”
Section: Introductionmentioning
confidence: 87%
“…Aside from its classical 2 of 20 action on sleep/wake cycles, melatonin has largely been shown to be a pleiotropic molecule [1][2][3][4] with multiple beneficial actions. In agreement, animal studies have shown melatonin to be an effective neuroprotectant in a number of neurodegenerative conditions such as hypoxia/ischemia [5][6][7], Alzheimer's Disease [8], Parkinson's Disease [9], and spinal cord injury [10]. Notably, clinical trials have been designed to establish the potential neuroprotective efficacy of melatonin in humans [11].…”
Section: Introductionmentioning
confidence: 87%
“…As melatonin can also display proinflammatory properties, for example, in arthritis, caution is due in all autoimmune diseases. In the case of Parkinson's disease (PD), numerous preclinical findings have indicated a beneficial role of melatonin, however, mainly in models based on mitochondrial dysfunction in the nigrostriatum and mostly without considering the early pre‐motor symptoms that reflect the initial stages of the disease. Moreover, several findings have remained contradictory .…”
Section: Melatonin and Inflammation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Neuroprotective effects of melatonin have been reported in the literature at the molecular, cellular, and tissue level in vitro and in animal models (reviewed by Mack et al [14]), to be achieved either by direct cellular scavenger mechanisms [15] or by melatonin receptor-mediated pathways [16]. At present, we have no indication or suggestion which of these or other mechanisms could be responsible for the remarkable improvement of the patient’s condition with melatonin treatment.…”
Section: Discussionmentioning
confidence: 99%